Molecular biology of the cell : the problems book - Wilson, John H., 1944-; Hunt, Tim, 1943- (New York, NY ; Abingdon, UK : Garland Science, 2015)
Designed to correspond with the first twenty chapter of Molecular Biology of the Cell, Sixth Edition.
Includes bibliographical references and index.
Keywords: Cytology -- Problems, exercises, etc; Molecular biology -- Problems, exercises, etc; Cytology; Molecular biology; Cells; Molecular Biology; Cytologie; Molekularbiologie; Problems and exercises